Late Preterm Infant With Postnatal Diagnosis of Renal Tubular Dysgenesis - Sheema Gaffar MD; Puneet Arora MD; Rangasamy Ramanathan MD (SAGE Publishing, 2022)
A male infant born at 34 weeks' gestation presented with acute cardiorespiratory decompensation soon after birth followed by renal failure. Initial clinical course was complicated by ventilator requirement, bilateral pneumothoraces, and hypotension managed with multiple inotropes. Persistent renal failure with oliguria and renal ultrasound showing noncystic medical renal disease prompted further investigation. Whole-exome sequencing showed 2 pathologic mutations in the angiotensin-converting enzyme (ACE) gene, suggesting a diagnosis of renal tubular dysgenesis (RTD). Renal tubular dysgenesis is usually a fatal condition affecting the renin-angiotensin system with possible autosomal recessive inheritance. Acquired cases have been described in the setting of in utero exposure to medications such as nonsteroidal anti-inflammatory medications (NSAIDs) and ACE inhibitors. Renal tubular dysgenesis should be suspected in any neonate presenting with renal failure, refractory hypotension, ventilator requirement, hypoplastic lungs, renal ultrasound showing normal-sized echogenic noncystic kidneys with poor corticomedullary differentiation, and antenatal history significant for oligohydramnios. The overall prognosis of patients with RTD continues to improve with better ventilatory management and renal replacement therapies.